KLF9 is a novel transcriptional regulator of bortezomib- and LBH589-induced apoptosis in multiple myeloma cells - Mannava, Sudha (American Society of Hematology, 2012)
Bortezomib, a therapeutic agent for multiple myeloma (MM) and mantle cell lymphoma, suppresses proteosomal degradation leading to substantial changes in cellular transcriptional programs and ultimately resulting in apoptosis. Transcriptional regulators required for bortezomib-induced apoptosis in MM cells are largely unknown. Using gene expression profiling, we identified 36 transcription factors that displayed altered expression in MM cells treated with bortezomib. Analysis of a publically available database identified Kruppel-like family factor 9 (KLF9) as the only transcription factor with significantly higher basal expression in MM cells from patients who responded to bortezomib compared with nonresponders. We demonstrated that KLF9 in cultured MM cells was up-regulated by bortezomib; however, it was not through the induction of endoplasmic reticulum stress. Instead, KLF9 levels correlated with bortezomib-dependent inhibition of histone deacetylases (HDAC) and were increased by the HDAC inhibitor LBH589 (panobinostat). Furthermore, bortezomib induced binding of endogenous KLF9 to the promoter of the proapoptotic gene NOXA. Importantly, KLF9 knockdown impaired NOXA up-regulation and apoptosis caused by bortezomib, LBH589, or a combination of theses drugs, whereas KLF9 overexpression induced apoptosis that was partially NOXA-dependent. Our data identify KLF9 as a novel and potentially clinically relevant transcriptional regulator of drug-induced apoptosis in MM cells.